2004
DOI: 10.1021/je034278t
|View full text |Cite
|
Sign up to set email alerts
|

Vapor Pressures of Pure Diethyl Sulfoxide from (298.15 to 318.15) K and Vapor−Liquid Equilibria of Binary Mixtures of Diethyl Sulfoxide with Water

Abstract: Total vapor pressure measurements and vapor−liquid equilibrium data are reported for the pure diethyl sulfoxide and diethyl sulfoxides + water binary system in the temperature range of (298.15 to 318.15) K. All mixtures show negative deviations from ideality due to strong interactions between diethyl sulfoxide and water molecules that are even stronger than those between dimethyl sulfoxide and water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…DESO, like DMSO, exhibits strong self-associative effects, even stronger than in DMSO and the existence of intense intermolecular DESO-DESO interactions, involving also SOÁ Á ÁHC hydrogen bonding has been suggested. Spectroscopic results together with thermodynamic measurements of DESO-water mixtures suggested very strong deviations from ideality, like in DMSO-water solutions, but to a greater extent [3][4][5].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…DESO, like DMSO, exhibits strong self-associative effects, even stronger than in DMSO and the existence of intense intermolecular DESO-DESO interactions, involving also SOÁ Á ÁHC hydrogen bonding has been suggested. Spectroscopic results together with thermodynamic measurements of DESO-water mixtures suggested very strong deviations from ideality, like in DMSO-water solutions, but to a greater extent [3][4][5].…”
Section: Introductionmentioning
confidence: 93%
“…The interest in the study of DESO/water mixtures comes from both physicochemical peculiarities [3][4][5][6][7] and recently recognised biomedical significance of this system [8,9]. DESO, like DMSO, exhibits strong self-associative effects, even stronger than in DMSO and the existence of intense intermolecular DESO-DESO interactions, involving also SOÁ Á ÁHC hydrogen bonding has been suggested.…”
Section: Introductionmentioning
confidence: 99%
“…This work is a continuation of our systematic study of physicochemical peculiarities of diethylsulfoxide (DESO) such as low temperature structural transition [1], dielectric relaxation [2], vapour pressures [3]. These studies, together with Raman and Fourier Transform Infrared (FTIR) measurements, had shown that DESO exhibits strong self-associative effects in the structure, even stronger than dimethylsulfoxide (DMSO).…”
Section: Introductionmentioning
confidence: 99%
“…(1) was determined graphically. The partial pressures of the solution components were calculated as described in [10,11]. The calculated partial pressures are listed in Table 3.…”
Section: Physical Chemistry Of Solutionsmentioning
confidence: 99%
“…Saturated vapor pressure was measured via the static method using mercury and oil pressure gauges, as described in [10,11]. The vapor pressure of pure DMSO was determined using an oil gauge; this parameter of pure alcohol and the solutions was measured with mercury gauges.…”
Section: Introductionmentioning
confidence: 99%